Improvement of Mathematics Learning Process and Outcomes Using the Realistic Mathematics Education Model in Grade II Students at SDN 205/II Bangun Harjo - Sila Hastutik; Randi Eka Putra; Sundahry Sundahry (CV. Master Literasi Indonesia, 2026)
Based on the initial observations made by the researcher, there are 20 students, and only 50% of them have achieved the KKTP (Learning Objective Achievement Criteria). Meanwhile, the school's KKTP is 75%. The purpose of this study is to describe the improvement in the learning process and cognitive learning outcomes through the application of the Realistic Mathematical Education Learning Model in class II of SDN 205/II Bangun Harjo. This study was conducted in two cycles using a classroom action research (CAR) design. Each cycle consisted of four phases: planning, implementation, observation, and reflection. Twenty second-grade students were the subjects of the study. Data collection methods included learning outcome assessments, recording, and observation. The Realistic Mathematics Education model was applied using learning outcome test questions and teacher and student observation sheets as data collection tools. The results of the study indicate that students' understanding of the subject matter can be improved through the application of the Realistic Mathematics Education Model. The increase in teacher observation scores from 87.5% in cycle I to 95% in cycle II, which is classified as excellent, demonstrates this. In addition, students' learning process scores increased from 77.5% (good) in cycle I to 92.5% (excellent) in cycle II. Furthermore, students' cognitive learning outcomes in mathematics increased from 60% (adequate) in cycle I to 90% (very good) in cycle II. Therefore, by applying the Realistic Mathematics Education Model, the mathematics learning process and outcomes can exceed the success indicators.